Preliminary study on the biology of Sycanus falleni Stal (Heteroptera, Reduviidae, Harpactorinae) - Lam, Truong Xuan (Academia Journal of Biology, 2015)
Preliminary study on the biology of Sycanus falleni Stal (Heteroptera, Reduviidae, Harpactorinae)